Development of alginate-based hydrogels/cryogels by gelation under pressure - Barros, Alexandre A. (2014)
A tissue-engineered polymeric scaffold should provide suitable macroporous structure similar to that of extracellular matrix which can induce cellular activities and guide tissue regeneration. Hydrogels are biocompatible hydrophilic polymer structures that can imbibe large amounts of water or biological fluids. Hydrogels are one of the upcoming classes of polymer-based systems that embrace numerous biomedical applications. This work is aimed to present a novel method to fabricate alginate-based calcium crosslinked hydrogels by manipulating gelation at high pressure. The cryogels can be obtained after freeze-drying. Cryogels for biomedical applications are of special interest due to large and highly interconnected pores that provide non-constrained mass transfer for cell growth and proliferation. However, to achieve desirable mechanical properties as well as high adsorption capacity, bimodal meso and macroporous materials are greatly desirable.